2015
DOI: 10.1037/a0038626
|View full text |Cite
|
Sign up to set email alerts
|

Men’s self-reported coping strategies for depression: A systematic review of qualitative studies.

Abstract: Key focal points of existing research on men's depression have included the role of masculinity and the nature of gender-specific coping styles. Existing quantitative studies may be limited in their ability to detect the full range of coping strategies deployed by men in response to this problem. The analysis of findings from qualitative studies may represent a useful way in which to obtain a more comprehensive representation of men's responses. To address this, a systematic review of qualitative studies exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 44 publications
2
39
0
Order By: Relevance
“…Both this review and other research indicates that men continue to hide their depression in public suggesting there may be a difference between the legitimacy they allow their distress in private and what they consider to be socially acceptable (Spendelow, 2015;Whittle et al, 2015). This suggests that dominant masculinity remains an important point of reference for the way in which men negotiate their experience of depression-even when they cannot, or do not wish to, aspire to this idealized representation of who they should be as men (Galasinski, 2008).…”
Section: Gender and Mental Health Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both this review and other research indicates that men continue to hide their depression in public suggesting there may be a difference between the legitimacy they allow their distress in private and what they consider to be socially acceptable (Spendelow, 2015;Whittle et al, 2015). This suggests that dominant masculinity remains an important point of reference for the way in which men negotiate their experience of depression-even when they cannot, or do not wish to, aspire to this idealized representation of who they should be as men (Galasinski, 2008).…”
Section: Gender and Mental Health Problemsmentioning
confidence: 99%
“…A recent systematic review of 14 qualitative studies looking at the way that men cope with depression noted that, while men are still constrained by traditional values that prevent them from acknowledging distress or seeking help, there are indications that that they can engage more flexibly with constructions of masculinity to better align them to their needs and experiences (Spendelow, 2015). Both this review and other research indicates that men continue to hide their depression in public suggesting there may be a difference between the legitimacy they allow their distress in private and what they consider to be socially acceptable (Spendelow, 2015;Whittle et al, 2015).…”
Section: Gender and Mental Health Problemsmentioning
confidence: 99%
“…However, most previous studies on male health promotion focuses on specific intervention settings and were delivered in face‐to‐face settings . Most research on mental health communication with men addresses depression and other mental health problems but does not explicitly look at suicide . Research evidence stems from a variety of western cultures, dominated by studies from the UK and the US and few are multilevel interventions including online media.…”
Section: Discussionmentioning
confidence: 99%
“…This study adds to current knowledge on communicating and engaging with men about mental health and suicide. Over recent years, increasing attention has been paid to the challenges of engaging men in mental health promotion . Research has shown that men are generally open and willing to talk about mental health issues but they may not feel comfortable doing so in conventional therapeutic settings .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation